Investigating factors that influence online purchase behaviour using Augmented and Virtual reality in the South African furniture industry - Mankhili, Mulalo Lusan (University of the Witwatersrand, Johannesburg, 2023)
In South Africa, the furniture industry plays a significant role in the country's economy, contributing to Growth Domestic Product (GDP) and employment rates. As the trend of online shopping continues to gain popularity, integrating augmented reality (AR) and virtual reality (VR) technologies into the retail sector has become increasingly important. Research has demonstrated that these technologies can offer a competitive edge to brands operating in the furniture sector. Consequently, this study aims to explore the factors influencing the adoption of AR and VR in the South African furniture industry. According to a report from the Department of Trade and Industry (DTIC), the South African furniture industry has experienced a decline in recent years, with consumers shifting towards purchasing furniture online through e-commerce platforms. Given the growing significance of e-commerce, it is imperative for businesses to understand the determinants of consumers' online purchasing behaviour to enhance their online sales performance. The purpose of this study is to investigate how the utilisation of AR and VR technologies can impact online purchase behaviour by dissecting the various factors influencing AR and VR adoption. To achieve this, the study has incorporated three theoretical frameworks: the Stimulus Organism Response theory (S-O-R), the Uses and Gratification theory (UGT), and the Flow theory. The research has identified several constructs derived from these theories to examine the interrelationships and influences among hedonic and utilitarian benefits, decision comfort, spatial presence, perceived intrusiveness, personal privacy concerns, mental imagery, perceived social presence, brand attitude, VR adoption, online purchase intention, and purchase behaviour. Data was collected from 400 South African online furniture customers, and the study utilised the Partial Least Squares Structural Equation Modelling (PLS-SEM) to analyse the relationships betweenthese variables. The study formulated eleven hypotheses, of which nine were supported. The findings revealed that hedonic and utilitarian benefits, decision comfort, spatial presence, mental imagery, perceived social presence, brand attitude, and VR adoption have an influence on online purchase behaviour. However, perceived intrusiveness and personal privacy concerns had no influence on online purchase intentions when using AR apps. This suggests that consumers' concerns about intrusiveness and privacy may not significantly affect their purchase intentions when interacting with AR technology. Additionally, the research highlights the roles of brand attitude and VR adoption as mediators between mental imagery and online behaviour and between iii perceived social presence and online purchasing behaviour. These findings offer valuable insights for businesses seeking to refine their online sales strategies and have the potential to contribute to the growth and development of the South African furniture industry
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce Research in the School of Business Sciences At the University of the Witwatersrand, 2023
Keywords: Augmented reality; Virtual reality; Furniture industry; Brand attitude; Decision comfort; Intrusiveness; Privacy concerns; Mental imagery; UCTD; SDG-9: Industry, innovation and infrastructure